SEEDLINGS OF PETUNIA X HYBRIDA IN BIODEGRADABLE TUBES TO REPLACE THE PLASTIC BAGS - Ferraz, M. V.; Cereda, M. P.; Iatauro, R. A. (Revista Brasileira de Engenharia de Biossistemas, 2015)
The objective of this study was to compare the development of petunia in biodegradable tubes with seedlings in plastic bags during the production phase. Distribution of dry matter in the three plant parts (leaves stem and root system) were evaluated. Also examined was the constitution of the cartridge and its loss of mass over time. The design was a randomized complete block. The analysis used 8 blocks with 16 plots in each block, plastic bags and biodegradable tubes. In total 128 plants were used for each package totaling 256 seedlings in this experiment. The data were submitted, with and without transformation and multiple comparisons between means by Tukey test at 5% level of significance. Data analysis showed that seedlings grown in biodegradable tubes had significantly less development.